(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Using their respective fictional universes as a starting point, this comparative study seeks to illuminate the intricate connection between story-building and the act of identity-creation in the writings of two prominent modern writers, Kazuo Ishiguro and Gao Xingjian. Consequently, the study’s end purpose is to reveal the authors’ use of storytelling approaches to portray the intricacy of human identity formation within the setting of large social and personal traumatic events. They are very different people—a lighter, non-noble Chinese expatriate Nobel laureate and a dark-skinned British author with Japanese ancestry and a Booker Prize—but they have the same thematic vector: displacement, memory, and finding one’s identity in a multicultural flux. For this reason, it is critical to highlight the writers’ unique storytelling styles while also drawing similarities to the subject’s depth. This study delves deeply into selected sources to demonstrate how Gao Xingjian and Kazuo Ishiguro have used narrative forms, character development, and themes to evoke existential dislocation and the quest for authenticity. This study aims to discover the ’universal’ character of humans trying to define their identity in the face of flux by comparing and contrasting the use of narrative in these two writers. By using vivid descriptions of landscapes, authors Gao Xingjian and Kazuo Ishiguro demonstrate how the nature of self is fluid and difficult to pin down, prompting readers to examine the integrity of their own life experiences and the veracity of the narratives about themselves that are shaped by society.